OPTIMALISASI SISTEM ADMINISTRASI PERKANTORAN MELALUI APLIKASI E-OFFICE PADA PROGRAM STUDI SEKRETARI POLITEKNIK PRATAMA MULIA SURAKARTA - Achaliyah, Siti; Rahayu, Bakti Sri; Ramadhani, Andira (Sekolah Vokasi, Universitas Sebelas Maret, 2023)
This research was initiated by analyzing the information needs of the secretarial study program focuses on education, community service, and research activities. Furthermore, information design planning is prepared according to the flow that will be used as the basis for making an Electronic Office (E-Office) in the Secretary Study Program of the Surakarta Pratama Mulia Polytechnic. In general, office work or activities related to services in obtaining, recording, storing, analyzing, and communicating information to agencies and companies definitely require information technology to complete work effectively and efficiently. The focus of this research is how to create an information system to make it easier to carry out document management activities and increase work effectiveness in an office environment. In this study, an office electronic information system was designed using Notepad++ software as a medium for storing source code. Code Igniter such as HTML, XAMPP, CSS, and PHP MySql software are used to accommodate the database of the required information system. Browser software of Mozilla Firefox is used as the search support software. The output of this study is an Electronic Office (E-Office) application that can help improve the process of managing and administering documents which have the advantage of archiving documents that can be done digitally anywhere and anytime, reducing the risk of damage and loss of documents, and maintaining data confidentiality well.